Dimensions of Culture and the Size of the Shadow Economy in the Member States of the European Union - Pukin, Paulina (Olsztyn Economic Journal, 2020)
This article discusses connections between dimensions of culture and the size of the shadow economy in the European Union member states. Critical perusal of the literature led to the development of the theoretical ground, while statistical analysis revealed connections between the shadow economy and the dimensions of culture. The research findings suggest a strong stochastic relation of the culture in a given country and the size of its shadow economy. Countries with a high level of complacency, distrust of the authorities, collectivism and aversion to uncertainty are characterized by shadow economies of a substantial size.